The Workers' Value of the Remaining Employment Contract Duration - Jos Van Ommeren; Mihails Hazans (Tinbergen Institute, 2005)
We introduce and apply a method for estimating workers' marginal willingness to pay for job attributes employing data on job search activity. Worker's willingness to pay for the remaining duration of the employment contract is derived. We provide evidence that workers attach substantial value to the remaining contract duration. A temporary worker with a remaining contract of six months is willing to pay about 10% of the monthly wage to increase the contract by one month.
Keywords: J3; J6; 330; On-the-job search; Job attributes; Contract duration; Temporary job; Suchtheorie; Arbeitsvertrag; Dauer; Befristete Beschäftigung; Theorie